ETIKA BERBAHASA PERSPEKTIF AL-QUR’AN - Dahliati Simanjuntak (Yurisprudentia: Jurnal Hukum Ekonomi, 2017)
The importance of polite language is very clear. Fine language is used as personal imaging, national identity, and unifying tools. Humans almost every time use and need communication. One communication tool that is often used is spoken language. In using language or talking with the other person, you must use good language, easy to understand and understandQaulan is an Islamic message which in its delivery is seen from communication according to Islamic teachings. Regarding how, in the Qur'an and al-Hadith various guidelines can be found so that communication runs well and effectively so that there is no misunderstanding between human beings in communicating the communication and communication they receive. We can term it as a rule, principle, or ethics of communicating in an Islamic perspective. The rules, principles, or ethics of communication in Islam are a guide for Muslims in communicating